Mixing planting with native tree species reshapes soil fungal community diversity and structure in multi-generational eucalypt plantations in southern China - Li, Chao; Xu, Yuxing; Wang, Zhichao; Zhu, Wankuan; Du, Apeng (Frontiers in Microbiology, 2023)
The continuous planting pattern of eucalypt plantations negatively affects soil quality. A mixed planting pattern using native species implanted in pure plantations has been considered a preferable measure for this problem. However, the impact of this approachon the structure and function of fungal communities is not clear. Here, harvesting sites that had undergone two generations of eucalypt plantations were selected to investigate soil fungal community structure and the co-occurrence network characteristics in response to two silvicultural patterns involving the third generation of eucalypt plantations (E) and mixed plantations of Eucalyptus. urograndis◊Cinnamomum. camphora (EC) and E. urograndis◊Castanopsis. hystrix (EH). Compared with the first generation of eucalypt plantations (CK), E markedly weakened enzyme activities associated with carbon-, nitrogen-. and phosphorus-cycling. reduced soil fungal alpha diversity, and elevated the relative abundance of Basidiomycota while decreasing the abundance of Ascomycota. In contrast, EC and EH not only enhanced fungal alpha diversity, but also reshaped fungal composition. At the class level, E caused an enrichment of oligotrophic Agaricomycetes fungi, classified into symbiotroph guild, while EC markedly decreased the abundance of those fungi and increased the abundances of Sordariomycetes, Dothideomycetes, Eurotiomycetes, and Tremellomycetes fungi, which were classified into saprotroph or pathotroph guild. Moreover, fungal network complexity and robustness topological attributes were higher or significantly higher in mixed plantations soils compared with those of pure eucalypt plantation E. Furthermore, fungal diversity, structure, and functional taxa were significantly affected by soil organic matter, pH, total nitrogen, and nitrate nitrogen.